Infants Receiving Very Early Antiretroviral Therapy Have High CD4 Counts in the First Year of Life. (29th August 2022) - Nelson, Bryan S; Tierney, Camlin; Persaud, Deborah; Jao, Jennifer; Cotton, Mark F; Bryson, Yvonne; Coletti, Anne; Ruel, Theodore D; Spector, Stephen A; Reding, Christina; Bacon, Kira; Costello, Diane; et al.
Abstract: : We followed 54 infants with in utero HIV after initiating very early antiretroviral treatment. At weeks 24 and 48, ≥80% had CD4 ≥1500 cells/mm 3 and CD4% ≥25%. Routine Pneumocystis jirovecii pneumonia prophylaxis in the first year of life may not be necessary for all very early treated infants. Clinical Trials Registration: NCT02140255.